Integrating School and Family Literacy to Foster Early Reading Habits: Evidence for SDG 4 from Indonesian Kindergartens - Ida Farida; Rusijono Rusijono; Karwanto Karwanto (Journal of Current Studies in SDGs, 2026)
Objective: This study aims to examine the implementation and outcomes of a School–Family Literacy Partnership model in fostering reading habits among children in early childhood education. It also investigates how the integration of school and family literacy practices supports sustainable reading habit formation. Method: A mixed-methods intervention design was employed involving two early childhood education institutions in Indonesia. Data were collected through observations, interviews, questionnaires, documentation, reading journals, and program evaluation records, and analyzed using descriptive statistics and thematic analysis. Results:  Integrating school literacy activities, home reading practices, parental involvement, monitoring, and reading recognition created a supportive literacy environment that strengthened children's reading engagement. Students achieved an average of 71 and 73 books per student, while program effectiveness reached 93.1% and 87.5%, indicating the important role of parental involvement in sustaining reading habits. Novelty: A School–Family Literacy Partnership Model is proposed to conceptualize reading habit formation as the outcome of coordinated interactions between school and family literacy environments. The model extends existing literacy interventions by emphasizing cross-context collaboration as a key mechanism for developing sustainable reading habits in early childhood education.